Radio frequency interference characteristics of plate-like soft magnetic powders-polymer composites - Kim, Sang Woo; Yoon, Y. W.; Kim, G. Y.; Lee, K. S. (TRANS TECH PUBLICATIONS LTD, 2006)
Radio frequency interference characteristics of plate-like Fe-Si-Al alloy powders-polymer composites were investigated for effective noise suppression. Broadband reflection loss characteristics were exhibited in the composites below a critical compaction pressure of 1.56 x 10(8) N/m(2), while narrowband characteristics were shown in the composites above the critical pressure. Although the composites at 2.34 x 10(8) N/m(2) had the highest complex permeability and complex permittivity, the loss properties did not show the broadband characteristics. The peculiar broadband characteristics were obtained in the composites with wideband dependency of the imaginary part of permittivity and permeability. These findings led us to conclude that the broadband electromagnetic interference characteristics of the composites are caused by the coupling effects of magnetic and dielectric resonance in the radio frequency range.
Keywords: NOISE SUPPRESSION